Ultra‐Luminous X‐ray sources and intermediate‐mass black holes. Issue 6 (August 2014) - Motch, C.
Abstract The extremely high X‐ray luminosity of non‐nuclear Ultra Luminous X‐ray sources (ULXs) may be evidence of the existence of black holes with masses intermediate between those produced by stellar evolution and those encountered in active galactic nuclei. Alternatively, they may reflect the existence of stellar mass black holes undergoing steady super‐Eddington accretion. In this short review, we will describe the main X‐ray and optical observational properties of these ULXs and discuss their likely accretion regimes. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)